Tastes of paradise a social history of spices, stimulants, and intoxicants - Schivelbusch, Wolfgang 1941- (Vintage Books, a division of Random House, Inc., 1993)
From the extravagant use of pepper in the Middle Ages to the Protestant bourgeoisie's love of coffee to the reason why fashionable Europeans stopped sniffing tobacco and starting smoking it, Schivelbusch looks at how the appetite for pleasure transformed the social structure of the Old World.